Changes in the cellular composition of the inflammatory infiltrate and connective tissue of the oral mucosa in rats during wound healing using a protective piezoelectric coating; Клиническая и экспериментальная морфология; Т. 11, № 1 - Koniaeva A. D. Anastasiya Denisovna; Varakuta E. Yu. Elena Yurjevna; Leyman A. E. Arina Evgenjevna; Bolbasov E. N. Evgeny Nikolaevich; Stankevich K. S. Ksenia Sergeevna (2022, 2022)
Introduction. Wound healing is a process based on a complex mechanism of intercellular interaction. The aim was to study changes in the oral mucosa cellular composition during wound healing with and without a protective piezoelectric coating